Exploring the role of biomass design in virtual reality forest bathing - Masters, Rachel A., author; Ortega, Francisco R., advisor; Interrante, Victoria, committee member; Lionelle, Albert, committee member; Moraes, Marcia, committee member; LoTemplio, Sara, committee member (Colorado State University. Libraries, 2024)
Stress is an increasingly prevalent problem that has severe health consequences if not managed properly. Every day, people are surrounded by work, health, financial, economic, and a variety of other stressors that deplete cognitive resources and put their nervous systems on high alert. Forest bathing, or nature immersion therapy, has been shown to reduce stress while restoring attentional resources, but despite these benefits, many people lack access to nature for a variety of reasons, including distance and health. VR has the potential to support access to virtual nature environments (VNE's) for people who cannot get into nature, yet the optimal design of biomass or plant life in VNE's is still an active area of research. Additionally, most of these VNE's require high end headsets and computers to run, which is not accessible technology for the everyday consumer. Given the current limitations of popular VR technology such as the Meta Quest 3, it is important to understand the relationship between plant asset realism and a VNE's restorative potential so that a balance can be achieved between a VNE that is deployable on everyday consumer headsets and a VNE that offers restorative benefit. This study was an initial exploration into high and low-realism VNE comparisons, accomplished by a mixed design study that compared two groups of participants, high and low-realism, against each other as well as against their own performance in a control condition where they closed their eyes. Through psychological and physiological measures, stress reduction and perceived attention restoration was assessed as a baseline, after a stressor test, then after the experiment condition to observe potential decreases in stress and increases in attention after the environment. Overall, there was only a significant increase in General Restorativeness in the high-realism environment when compared against the control and the low-realism environment, but trends in the data call for future research on this topic.
Keywords: forest bathing; nature immersion; virtual reality; mental health; attention restoration; stress reduction